Era Digitalisasi Media Pemasaran Online Pengembangan Usaha Mikro Kecil - Toto Sukarnoto; Nurjati Nurjati; Vita Rani (IAI Bunga Bangsa Cirebon, 2021)
This study aims to determine strategies in increasing student learning motivation to maintain the The era of digitalization brings a wind of change, many polemics and pros and cons to the development of all sectors related to digital is no exception to the business sector and the economy. In running a business, marketing is the spearhead in penetrating the market, applies whether it is a large company or a company with micro, small or medium scale. Micro enterprises still face classic problems that have often occurred regarding capital limitations and still very simple marketing patterns that apply. The research method used in this research is a descriptive qualitative research method that is a research that produces descriptive data (depictions) in the form of written and oral facts of observed behavior, in a situation that takes place fairly and scientifically and not in controlled conditions.The banana industry and trade of sale